2006
DOI: 10.1177/089686080602600415
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Insulin over 24 Hours in Standard and Bicarbonate-Based Peritoneal Dialysis Solutions Contained in Bags Made of Different Materials

Abstract: Background The purpose of this study was to evaluate potency changes in insulin in different solutions and bag materials used for peritoneal dialysis (PD). One of the PD solutions (Physioneal) tested is available in two different solution containers, PVC and Clear-Flex. Four insulin concentrations (4 IU/L, 10 IU/L, 20 IU/L, and 40 IU/L) were evaluated. This range of concentrations was defined in accordance with standard medical practice. All PD solutions made by Baxter, Castlebar, Ireland. Methods Insulin dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…While no significant differences in adsorption of insulin are observed between PVC and polyolefin containers (30), adsorption to glass surfaces is much faster and more pronounced (29). Recently, Voges et al demonstrated that insulin agglomeration (31), which occurs with increasing pH, was concomitant with increased adsorption (30). Generally, if adsorption occurs, the adsorption behavior of any drug seems similar to that of insulin in terms of time, temperature, and concentration.…”
Section: Intraperitoneal Drug Administrationmentioning
confidence: 99%
See 3 more Smart Citations
“…While no significant differences in adsorption of insulin are observed between PVC and polyolefin containers (30), adsorption to glass surfaces is much faster and more pronounced (29). Recently, Voges et al demonstrated that insulin agglomeration (31), which occurs with increasing pH, was concomitant with increased adsorption (30). Generally, if adsorption occurs, the adsorption behavior of any drug seems similar to that of insulin in terms of time, temperature, and concentration.…”
Section: Intraperitoneal Drug Administrationmentioning
confidence: 99%
“…Table 2 lists stability data of drugs studied as single additives to PD solutions in PVC containers (30,35-38,45-50,52,54-71). For drugs for which stability differs with concentration and/or PD solution formulation, corresponding stabilities are given; otherwise, the reported stability is applicable to all combinations.…”
Section: Drug Compatibility and Drug Stability Data In Pd Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction in insulin requirement is most pronounced compared with subcutaneous administration when insulin is instilled into the empty abdominal cavity, but if insulin is instilled with dialysis solution, there are losses of activity due to adsorption to the plastic surface of delivery systems [ 25 ]. Besides, bioavailability of intraperitoneal insulin might differ according to the solution bag used [ 26 ]. Importantly, hepatic subcapsular steatosis may be a complication associated with intraperitoneal insulin [ 27 ].…”
Section: Potential Benefits Of Peritoneal Dialysis In Diabeticsmentioning
confidence: 99%